The study of veneer machine from oil palm stem - P Dangwilailux; W Kalasee; V Akvanich (My University, 2019)
Abstract This study aim was to design an oil palm stem peeling machine. Oil palm veneer was selected from 28-year-old palm trunk, the height was 8 meters, and the diameter approximately 400-500 mm. The prototype veneer machine was to make the palm timber as a thin wood sheet for supplying to the plywood manufacturing industry. The veneer machine was composed of 3 units, which were 1) the roller unit 2) the blade unit, and 3) the feed screw unit. It was driven by 5 hp motors to rotate 2 rollers with speeds of 100, 120, and 140 rpm. The palm wood was rotated in the opposite direction to the blade using a 10 hp motor. It moved to the centre of the timber with forward speeds of 0.17, 0.29, and 0.59 m/min. Finally, the oil palm stems were peeled as veneer with a thickness of 1-3 mm and length of 2400 mm. The results were that the machine was able to produce the veneer product without it being broken and it had a high strength by using the roller speed of 120 rpm combine with a feed rate of 0.29 m/min.
Keywords: Laminated veneer lumber; Oil Palm Production and Sustainability